Implementasi Importance Performan Analysis (IPA) Sebagai Penunjang Ekowisata Berkelanjutan di Agropark Sabah Balau - Lenty Hoya, Ade; Abidin, Jaenal (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
Sustainable tourism is the eighth sustainable development goal regarding Decent Work and Economic Growth in the target of promoting tourism and culture and local products in a sustainable manner. Sustainable tourism aims to maintain a balance between the economy, the environment and society by protecting nature and local culture, supporting communities and promoting responsible and long-term beneficial tourism experiences. This research analyzes the level of visitor satisfaction with services available at the Sabah Balau agropark tourism, South Lampung. The method used is Importance Performance Analysis (IPA). The results of research on the Sabah Balau agropark tourism were 82% for service quality, and managers need to improve cleanliness in the tourist attraction environment, cleanliness of toilets at the location, and the attitude of the staff so that it becomes an added value for this tourism. Keywords: Ecotourism, Importance Performance Analysis, Sustainable Development